What Influences Decision-Making for Cochlear Implantation in Adults? Exploring Barriers and Drivers From a Multistakeholder Perspective. Issue 6 (November 2020) - Ebrahimi-Madiseh, Azadeh; Eikelboom, Robert H.; Bennett, Rebecca J.; Upson, Gemma S.; Friedland, Peter L.; Swanepoel, De Wet; Psarros, Colleen; Lai, Wai Kong; Atlas, Marcus D.
Abstract : Objectives: To explore the factors influencing the uptake of cochlear implants in adults, determine the impact of each factor, and to conceptualize the journey to implantation from a multistakeholder perspective. Design: Concept mapping was used to integrate input from multiple stakeholders, each with their own experience and expertise. This mixed participatory method collects qualitative and quantitative data collection and enables further quantitative analysis. There were two participant cohorts: clients (cochlear implant recipients, candidates, and family members) and professionals (cochlear implant audiologists, ear, nose, and throat surgeons, administration staff, managers. and manufacturer representatives). A total of 93 people participated in the study: client cohort (n = 60, M age = 66.60 years) and professional cohort (n = 33, M age = 45.24 years). Participants brainstormed statements in response to the question "What influences people's decision to get/not get a cochlear implant?" They subsequently grouped the statements and named each group. They rated each statement as to its impact on the decision and prioritized the need for each to be changed/improved using a five-point Likert scale. Multidimensional scaling was used to produce a visual representation of the ideas and their relationship in the form of concepts. Further analysis was conducted to determine the differences between the cohorts, subcohorts, and concepts. Results: One hundred ten unique statements were generated and grouped into six concepts which either directly affected the client or their environment. These concepts were: external influences (awareness and attitude of non-implant professionals about uptake, cost, logistics, the referral pathway, public awareness); uncertainties, beliefs, and fears (fears, negative effect of word of mouth, unsuccessful previous ear surgery, cosmetics of the device, misunderstanding of how a cochlear implant functions, eligibility for an implant and outcomes after implantation); health problems (mental and physical health); hearing difficulties (social, emotional, and communication impacts of hearing loss, severity of hearing loss, benefit from and experience with hearing aids); implant professionals (implant team's attitude, knowledge and relationship with clients, quality of overall service); and goals and support (clients 'hearing desires and goals, motivation, positive impact of word of mouth, family support, having a cochlear implant mentor. The six concepts fell into two overarching domains: the client-driven domain with four concepts and the external domain with two concepts. The mean rating of concepts in terms of impact on a client's decision to get an implant ranged from 2.24 (external influences, the main barrier) to 4.45 (goals and support, the main driver). Ratings significantly differed between the client and professional cohorts. Conclusions: This study increases our understanding of the factors, which influence a client's decision choose a cochlear implant as a hearing treatment. It also provides new information on the influence of the other stakeholders on the client journey. The magnitude of the generated statements in the client-driven domain highlights the pivotal role of individualized care in clinical settings in influencing a client's decision and the need for the professionals to understand a client's needs and expectations. A client's persistent hearing difficulties, goals, and support network were identified as drivers to the uptake of cochlear implants. However, the barriers identified highlight the need for a collaborative multi- and interdisciplinary approach to raise awareness in and educate non-implant hearing professionals about the cochlear implant process, as well as providing information to empower clients to make educated decisions and consider a cochlear implant as a hearing management option. Abstract : Supplemental Digital Content is available in the text.